The Way Forward for Indian Ocean Island Tourism Economies : Is There a Role for Regional Integration? - World Bank (Washington, DC, 2014)
In addition to some of the most acclaimed beaches in the world, the Indian ocean islands offer one of the planet's greatest concentrations of biodiversity and stunning landscapes that include active volcanoes, sculpted canyons, and verdant seaside cliffs. Yet, despite its many attributes and accolades, the region is not very well known within the global tourism marketplace. This note is an analysis aimed at assessing opportunities for tourism integration among the four Indian ocean island nations of Comoros, Madagascar, Mauritius, and Seychelles. To inform this regional analysis and recommendations, the four reviews were conducted to provide a basis for understanding each country's tourism sector in terms of its development and current performance, contribution to the economy, and principal challenges. As a basis for analysis of the prospect of regional integration, the current state of tourism in each of the countries is considered within a regional context and recommendations for specific regional tourism integration initiatives are provided as guidance for the way forward. The tourism sector reviews were completed through a combination of desk research and country visits that involved consultations with a range of stakeholders from the public sector, private sector, civil society, and donor community. Each country review also contains a set of recommendations for addressing the identified challenges. Included in the key issues identified for each country's tourism sector are those issues that have regional implications. This report is organized as follows: section one gives introduction to the regional integration study; section two gives regional integration: the promises and the reality; section three presents overview of four countries' tourism sectors; section four presents regional tourism integration overview; section five gives key issues for regional integration; section six gives recommendations; section seven gives way forward; and section eight gives conclusion.